Occurrence of the foramen of vesalius and its morphometry relevant to clinical consideration - Vipavadee Chaisuksunt (2018)
All 377 dry skulls were examined for the occurrence and morphometry of the foramen of Vesalius (FV) both in the middle cranial fossa and at the extracranial view of the skull base. There were 25.9% and 10.9% of FV found at the extracranial view of the skull base and in the middle cranial fossa, respectively. Total patent FV were 16.1% (11.9% unilaterally and 4.2% bilaterally). Most FV were found in male and on the left side. Comparatively, FV at the extracranial view of the skull base had a larger maximum diameter. The distance between FV and the foramen ovale (FO) was as short as 2.05±1.09 mm measured at the extracranial view of the skull base. In conclusion, although the existence of FV is inconstant, its occurrence could not be negligible. The proximity of FV to FO should remind neurosurgeons to be cautious when performing the surgical approach through FO. Copyright © 2012 Vipavadee Chaisuksunt et al.